The Effect of Job Stress on Diet Quality and Emotional Eating Among Hospital Employees - Aliye Ozenoglu; Cahit Erkul (International Journal of Gastronomy Research)
Hospital employees are considered one of the high-stress occupational groups due to their challenging working conditions and their responsibility for human health. Emotional eating, which describes the tendency to overeat in response to negative emotions, is expected to be more prevalent among hospital employees because of stressful working conditions. It is likely that emotional eating, alongside stressful working conditions, may negatively impact diet quality. This study aimed to investigate the effect of job stress on diet quality and emotional eating among hospital employees. In this study, 272 volunteers participated, consisting of 112 men and 160 women, with an average age of 34.26±11.50 years. According to the Mediterranean Diet Quality Index (KID-MED), only 24.6% of the participants had optimal diet quality. In comparison, 28.3% were categorized as non-emotional eaters based on their Emotional Eating Scale (EES) scores. A positive and significant correlation was found between Body Mass Index (BMI) and EES scores (p<0.001). Participants who worked exclusively during the day had significantly lower job stress and EES scores than other participants (p<0.05), while their KID-MED scores were significantly higher (p<0.001). As workload increases, the role of evolutionary survival mechanisms in decreasing KID-MED scores becomes evident, suggesting that higher levels and intensity of stress lead to a predominance of homeostatic eating. Our findings support the negative impact of job stress on emotional eating and diet quality among healthcare workers.